Non-celiac gluten sensitivity - Bigio,Cecilia (2023)
Abstract Introduction: Recurrent abdominal pain accounts for up to 5% of consultations in pediatric primary care. An organic cause is found in only 5−10% of children. Non-celiac gluten sensitivity is a condition characterized by intestinal symptoms (including abdominal pain) and extra-intestinal symptoms related to the ingestion of gluten-containing foods in subjects who are not affected by celiac disease or wheat allergy. Treatment is based on a gluten-free diet. Objectives: The aim of this work was to review relevant studies in Pediatrics on the subject published in recent years, with the purpose of increasing knowledge among pediatric specialists and contributing to raising awareness and maintaining a high index of clinical suspicion of the condition and improving the diagnosis and management of the condition while reducing the use of gluten-free diet without medical advice. Development: A review was carried out on PubMed and Cochrane databases using terms related to non-celiac gluten sensitivity, and the evidence about gluten, non-celiac gluten sensitivity, biomarkers, epidemiology, and Salerno Criteria (used in the diagnosis of the disease) was assembled and reported. Conclusion: Establishing the diagnosis of non-celiac gluten sensitivity and other gluten-related disorders is crucial to design measures to facilitate access to gluten-free diets for patients who really need them. More standardized clinical trials in Pediatrics are needed to draw specific conclusions about the disease.